Analysing sexual communication messages in Durex condom advertisement from marital standpoints - Alwi Putra Ramadhan; Novin Farid Styo Wibowo; Moch Fuad Nasvian; Mohd Hilmi Bakar (Faculty of Communications Science, Dr. Soetomo University, 2024)
This research aims to explore the reception of sexual communication messages within the context of marital relationships in the Durex